Analysis of Numeration Ability form the Results of the Minimum Competency Assessment (AKM) in Class V Students of at SD Negeri 101 Palembang - Alhafits, Ridho; Rohana, Rohana; Hera, Treny (Edumaspul: Jurnal Pendidikan, 2023)
The numeracy abilities in the AKM results for class V students at SD Negeri 101 Palembang are classified as below the set standards. Because students do not understand the AKM numeracy questions at the level of knowing, applying and reasoning. students are not yet adept at doing numeracy questions. Fulfillment of infrastructure for working on numeracy questions, especially inadequate IT. The aim of the research is to analyze the numeracy abilities of class V students at SDN 101 PLG in terms of perceptions of Creating, Applying and Reasoning as well as analyzing the level of students' numeracy abilities. The method used is descriptive with a quantitative approach. Research with a quantitative approach, pressure analysis on numerical data (numbers) which is then analyzed using appropriate statistical methods. The sample consisted of 30 fifth grade students and data analysis used the SPSS program. The numeracy abilities of class V students at SD Negeri 101 Palembang are mostly obtained based on the results of calculations between the students' average scores and the standard deviation of the data, then the results will be determined based on norm references. At the knowledge question level, for the "high" category there were 2 students or 6.67%, for the "medium" category there were 13 students or 43.33% and for the "low" category there were 15 students or 50%. At the application question level for the "high" category there were 3 students or 10% for the "medium" category there were 14 students or 46.67% and there were 13 students or 43.33% for the "low" category. At the level of reasoning questions for the "high" category there were 3 students or 10%, for the "medium" category there were 14 students or 50% and for the "low" category there were 12 students or 40%. The results of the overall numeracy ability test assessment show that the numeracy ability of students in the "high" category is 6 students or 20%, in the "medium" category is 18 students or 60% and in the "low" category is 6 students or 20%. So it can be concluded that the majority of students at SD Negeri 101 Palembang have a medium numeracy ability category.Keywords: Numeracy, Numeracy Ability, AKMABSTRAKKemampuan numerasi pada hasil AKM pada siswa kelas V di SD Negeri 101 Palembang tergolong dibawah standar yang di tetapkan. Dikarenakan siswa kurang memahami soal AKM numerasi level knowing, applying dan reasoning. siswa belum terlatih mengerjakan soal – soal numerasi. Pemenuhan sarana prasaranan mengerjakan soal – soal numerasi, terutama IT yang belum memadai. Tujuan dari penelitian untuk menganalisis kemampuan numerasi siswa kelas V SDN 101 PLG ditinjau dari persepsi Knowing, Applying dan Reasoning serta menganalisis tingkat kemampuan numerasi siswa. Metode yang digunakan ialah deskriptif dengan pendekatan kuantitatif. Penelitian dengan pendekatan kuantitatif menekankan analisis pada data numerik (angka) yang kemudian dianalisis dengan metode statistik yang sesuai. Sampel sejumlah 30 siswa kelas V dan analisis data menggunakan program SPSS. Kemampuan numerasi siswa kelas V SD Negeri 101 Palembang yang mayoritas sedang diperoleh berdasarkan hasil hitung antara nilai rata-rata siswa dengan standar deviasi data kemudian hasilnya akan dikategorikan berdasarkan acuan norma. Pada level soal knowing untuk kategori “tinggi” terdapat 2 siswa atau 6,67% untuk kategori “sedang” terdapat 13 siswa atau 43,33% dan untuk kategori “rendah” terdapat 15 siswa atau 50%. Pada level soal applying untuk kategori “tinggi” terdapat 3 siswa atau 10% untuk kategori “sedang” terdapat 14 siswa atau 46,67% dan terdapat 13 siswa atau 43,33% untuk kategori “rendah”. Pada level soal reasoning untuk kategori “tinggi” terdapat 3 siswa atau 10% untuk kategori “sedang” terdapat 14 siswa atau 50% dan untuk kategori “rendah” terdapat 12 siswa atau 40%. Hasil penilaian tes kemampuan numerasi secara keseluruhan menunjukkaan bahwa, kemampuan numerasi siswa untuk kategori “tinggi” sebanyak 6 siswa atau sebesar 20% kategori “sedang” sebanyak 18 siswa atau 60% dan kategori “rendah” sebanyak 6 siswa atau 20%. Sehingga, dapat disimpulkan bahwa mayoritas siswa SD Negeri 101 Palembang memiliki kategori kemampuan numerasi sedang.Kata Kunci: Numerasi, Kemampuan Numerasi, AKM